Perancangan Ulang Fasilitas Kerja Alat Pembuat Gerabah dengan Mempertimbangkan Aspek Ergonomi - Muhammad Hanafi; Rahmaniyah Dwi Astuti; Irwan Iftadi (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2011)
One of the pottery found in central Java in Bayat, Klaten. The process of making pottery is still done manually. In previous research, Febrianti (2009) has designed the turntable to generate employment and chair rotation driven manually by a foot to workers by applying pottery maker RULA method. Output results of this study was the design and yet was tested against pottery workers, so can not guarantee whether the tool has an ergonomic or not. In this experiment, pottery maker who still form the design image and then made a real pottery maker. The tool was tested against the six workers. From the test results obtained by some of the weaknesses of the old design tools. So that should be added some specs to get comfortable in operating the old design tool.